Students’ Concept Maps Profile on Environmental Pollution Material During the COVID-19 Pandemic - Sunarni, Sunarni; Widoretno, Sri; Karyanto, Puguh; Sugiharto, Bowo; Dwiastuti, Sri; Prabowo, Chandra Adi (Jurnal Pendidikan Sains, 2024)
The study investigates the performance of students in constructing Concept Maps (CM) related to environmental pollution material during the COVID-19 pandemic. The data reveals that the overall achievement in CM construction was suboptimal, with no component reaching more than half of its maximum potential. The highest achievement was recorded in the valid relationship component, which attained 9.75% of its maximum possible score. This was followed by the hierarchy component, achieving 7.34%, and the branching component at 3.42%. The pattern component ranked fourth with 1.31%, closely followed by the example component at 1.30%. The lowest performance was observed in the crosslink component, with an achievement of 0.00%. The analysis suggests that students struggled significantly with constructing comprehensive and complex CM, indicating a need for further instructional support. The low scores, particularly in critical components such as crosslinks and examples, highlight gaps in students’ ability to synthesize and analyze information, which are vital for developing more advanced CM. These findings point to the importance of enhancing students’ conceptual understanding and analytical skills to improve their learning outcomes, especially in the context of environmental pollution education during the challenges posed by the pandemic.DOI: 10.17977/jps.v12i42024p141